Efek Moderasi Size dalam Pengungkapan Sukarela: Bukti Empiris di Bursa Efek Indonesia - Wendy, Wendy (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to analyze the determinants of voluntary disclosure (VD) by using three non-interaction models and one interaction model. This paper observes four VD"™s determinants (ownership dispersion, managerial ownership, audit committee, and independent commissioners), one control variable (capital structure), and one moderating variable (total asset). By using panel data analysis (225 observations) on the Indonesia Stock Exchange (IDX), it is found that the total asset can be used as the moderating variable in explaining the determinants of VD in IDX. Furthermore, the interaction model shows better results than non-interaction models. Managerial ownership, independent commissioners, and ownership dispersion show high consistency with the tested hypotheses. This is different from the audit committee which does not support the hypothesis. These findings implicate managerial policies that need to consider good corporate governance in supporting the voluntary disclosure of public companies in Indonesia. Strengthening external validity in the form of replication, developing research models, and refining research methods is needed to strengthen the managerial implications. Testing the robustness by simulating various substitute proxies to optimize the generalization of research findings needs to be considered in future studies.